2020
DOI: 10.1097/aln.0000000000003065
|View full text |Cite
|
Sign up to set email alerts
|

Influence of St. John’s Wort on Intravenous Fentanyl Pharmacokinetics, Pharmacodynamics, and Clinical Effects

Abstract: Background Patients often use complementary and alternative herbal medicines, hence, potential exists for adverse herb–drug interactions. Fentanyl is metabolized by hepatic CYP3A4 and considered transported by blood–brain barrier P-glycoprotein. Both disposition processes could be upregulated by the herbal St. John’s wort. This investigation evaluated effects of St. John’s wort on fixed-dose and apparent steady-state IV fentanyl pharmacokinetics, pharmacodynamics, and clinical effects. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 49 publications
0
8
0
Order By: Relevance
“…Compartmental parameter estimates for the fentanyl three-compartment analysis using Loughren priors [ 22 ] are shown in Table 3 and those for the confirmatory analysis using Shafer et al priors [ 23 ] in Table S2 of the ESM. Figure 3 shows satisfactory visual predictive check plots for these PK data.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Compartmental parameter estimates for the fentanyl three-compartment analysis using Loughren priors [ 22 ] are shown in Table 3 and those for the confirmatory analysis using Shafer et al priors [ 23 ] in Table S2 of the ESM. Figure 3 shows satisfactory visual predictive check plots for these PK data.…”
Section: Resultsmentioning
confidence: 99%
“…Fentanyl priors were sourced from two publications. Loughren and colleagues estimated fentanyl parameters and their variability in a study investigating the impact of St John’s wort on pharmacokinetics [ 22 ]. Shafer and colleagues estimated fentanyl parameters using pooled data during infusion [ 23 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Successively, it was demonstrated that the induction of CYP3A and P-gp by SJW, in healthy volunteers, depends on hyperforin concentration in the different type of extracts used [28][29][30], and, in particular, it was suggested that a daily dose of 1 mg of hyperforin is a critical cut-off for clinically significant interactions [31]. A recent randomized, double-blind, parallel-arm, clinical trial enrolling 16 healthy volunteers has evaluated the effect of SJW on fentanyl, the latter being metabolized by hepatic CYP3A4 and transported by P-gp [32]. Under these circumstances, the pharmacokinetics and pharmacodynamics of fentanyl do not result affected.…”
Section: St John's Wort (Sjw)mentioning
confidence: 99%
“…The following are available online at , Table S1: Pharmacokinetic Pathways for Drugs Implicated in Herb–Drug Interactions Where Herb Was Clinically Studied; Table S2: Findings of Clinical Studies; Table S3: Comparison of Case Reports to Herb–Drug Interaction Checkers; Table S4: Case Report Summaries; Table S5: Materials and Methods of Clinical Studies. (References [ 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 , 93 , 94 , 95 , 96 , 97 , 98 , 99 , 100 , 101 , 102 , 103 , 104 , 105 , 106 , 107 , 108 , 109 , 110 , 111 , 112 , 113 , 114 , 115 , 116 , 117 , 118 , 119 , 120 , 121 , 122 …”
mentioning
confidence: 99%